Pengaruh Pertumbuhan Perusahaan, Kebijakan Dividen dan Struktur Modal terhadap Nilai Perusahaan - Taufik Hidayat; Dila Angraini (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the inconsistency of empirical findings regarding the determinants of firm value, particularly among large-cap companies listed in the IDX30 index, which experienced significant valuation fluctuations during the 2020-2024 period. The objective of this research is to examine the effect of company growth, dividend policy, and capital structure on firm value, both partially and simultaneously. The study employs a quantitative approach using secondary data derived from the annual financial statements of IDX30 companies. A purposive sampling method was applied, resulting in 16 firms observed over five years. Panel data regression analysis was conducted using the Fixed Effect Model, selected based on Chow and Hausman tests, and processed with EViews 13. The results indicate that, simultaneously, company growth, dividend policy, and capital structure significantly influence firm value. However, partial testing reveals that company growth and dividend policy do not have a significant effect on firm value. In contrast, capital structure shows a significant negative effect, suggesting that higher leverage levels tend to reduce firm value due to increased financial risk perceived by investors. These findings highlight the importance of prudent debt management in maintaining firm value among blue-chip companies, particularly in periods of economic uncertainty.